The Pomegranate READERS’ FORUM - Editors, The (Pomegranate, 1999)
Please contribute to our Readers’ Forum so that we may continue to present this valuable venue for the exchange of ideas. Letters may be edited to conserve space or to avoid repetition. Writers of published letters will have their subscriptions extended by one or two issues.